High Concentrations of H2O2 Make Aerobic Glycolysis Energetically More Favorable for Cellular Respiration - Molavian, Hamid R.; Kohandel, Mohammad; Sivaloganathan, Sivabal (Frontiers in Physiology, 2016)
Since the original observation of the Warburg Effect in cancer cells, over eight decades ago, the major question of why aerobic glycolysis is favored over oxidative phosphorylation has remained unresolved. An understanding of this phenomenon may well be the key to the development of more effective cancer therapies. In this paper, we use a semi-empirical method to throw light on this puzzle. We show that aerobic glycolysis is in fact energetically more favorable than oxidative phosphorylation for concentrations of peroxide (H2O2) above some critical threshold value. The fundamental reason for this is the activation and high engagement of the pentose phosphate pathway (PPP) in response to the production of reactive oxygen species H2O2 by mitochondria and the high concentration of H2O2 (produced by mitochondria and other sources). This makes oxidative phosphorylation an inefficient source of energy since it leads (despite high levels of ATP production) to a concomitant high energy consumption in order to respond to the hazardous waste products resulting from cellular processes associated with this metabolic pathway. We also demonstrate that the high concentration of H2O2 results in an increased glucose consumption, and also increases the lactate production in the case of glycolysis.